2018
DOI: 10.3389/fphys.2018.01090
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E Inhibits Proliferation and Migration of Intestinal Epithelial Cells via Activating Cofilin

Abstract: The proliferation and migration of intestinal epithelial cell is important to the barrier integrity of intestinal epithelium. Cucurbitacin E (CuE) is one of the tetracyclic triterpenoids extracted from the cucurbitaceae that has been shown to inhibit cancer cell growth, tumor angiogenesis and inflammatory response. Nevertheless, the role of Cucurbitacin E in regulating the proliferation and migration of intestinal epithelial cells remain unclear. In this study, the human intestinal epithelial cell line Caco-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Damnacanthal, a major component of morinda citrifolia, can inhibit migration and invasion of MDA‐MB‐231 breast carcinoma cells by suppressing phosphorylated cofilin 33 . Cucurbitacin I and E can inhibit kinetic activity of LIMK to phosphorylate cofilin and then retarded proliferation and migration of HeLa cells and Caco‐2 human epithelial colorectal adenocarcinoma 34,35 . Though so many LIMK1 inhibitors exist, few inhibitors act on non‐small cell lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damnacanthal, a major component of morinda citrifolia, can inhibit migration and invasion of MDA‐MB‐231 breast carcinoma cells by suppressing phosphorylated cofilin 33 . Cucurbitacin I and E can inhibit kinetic activity of LIMK to phosphorylate cofilin and then retarded proliferation and migration of HeLa cells and Caco‐2 human epithelial colorectal adenocarcinoma 34,35 . Though so many LIMK1 inhibitors exist, few inhibitors act on non‐small cell lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Natural compound, diallyl disulfide from garlic extract also reduced the colorectal cancer cell migration and invasion 35,36 . However, still it needs to expand more animal experiments and pharmacokinetics analysis for applying the cancer patient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were performed according to previously published methods using β-actin as an internal control (Cao et al, 2013; Song et al, 2018). Briefly, Caco-2 cells were inoculated into six-well culture plates.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to our results, other studies have shown that CuE can induce apoptosis in 95D human lung cancer cells, SAS oral squamous cell carcinoma cells, and SW527 breast cancer cells. Furthermore, our previous study showed that CuE could induce G2/M cell cycle arrest in Caco-2 cells ( Song et al, 2018 ). Other studies demonstrate that prolonging the cell cycle may lead to secondary apoptosis ( Liu et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…CuE has various pharmacological properties, including anti-inflammatory, antitumor, and antioxidant effects ( Attard and Martinoli, 2015 ). Our recent research results showed that CuE inhibits the proliferation and migration of human IECs by activating cofilin, and in hypoxic conditions, activated cofilin regulates the permeability of the intestinal epithelium by depolymerizing F-actin ( Song et al, 2018 , 2019 ). However, the effects of CuE on apoptosis and autophagy in IECs are still unclear and deserve further investigation.…”
Section: Introductionmentioning
confidence: 99%